To evaluate the prevalence of female genital tuberculosis in Hyderabad - S., Srinivas Rao M.; K, Pavani; M, Uma; Kumari, Krishna; V., Vinayaraj E.; Dass, Manick (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis (TB) is an increasing public health concern worldwide. It is one of the most important causes of infectious morbidity and mortality. Genital TB is one form of extra pulmonary TB and is not uncommon, particularly in communities where pulmonary TB is prevalent. The objective of the study was to evaluate the prevalence of female genital tuberculosis in Hyderabad and its presentational symptoms and methods of diagnosis. Methods: A total of 1102 cases of suspected genital TB who had been registered and treated in the AIMSR and few selected government urban health post and private hospitals and clinics in different zones of Hyderabad, from 2012 January to 2013 March were retrospectively and prospectively studied. From this group, 23 women were diagnosed as having genital TB based on the standard pathological and microbiological criteria of tissue specimens. Results:Out of 23 cases diagnosed as having genital tuberculosis, 3 patients (13.04 %) presented with abdominal or pelvic pain. In 17cases (73.91%) tuberculosis was diagnosed during studies performed to evaluate the cause of their infertility, and the most common diagnostic procedure was endometrial curettage. Remaining 3 cases (13.05 %) have past, present or contact history of tuberculosis. Female genital TB accounted for 2.08 % of all tuberculosis patients in this study. Conclusions: This study indicates the presence of a strong relationship between genital TB and infertility; therefore genital TB would be more frequently diagnosed if this possibility was considered in the evaluation of every infertile patient in areas where tuberculosis is endemic.